(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This research was experimental research which had purpose to know effectiveness of the Reciprocal Teaching model towarded the student’s creative thinking ability in math, grade 7th students SMP Perguruan Rakyat Pancur Batu. The population in this research was the students of class VII SMP Perguruan Rakyat Pancur Batu consisted of two class with the total of the population was 48 students. The sampling technique in the population in this study used the cluster random sampling method. The instrument of this research was pretest and posttest. The conclusion obtained show the results of the study that, Reciprocal Teaching learning model is better than conventional learning models of student’s creative thinking abilities, students’ creative thinking skills using the Reciprocal Teaching learning model can exceed 75 in terms of achieving KKM and student learning completeness criteria and There is an active influence on the ability to think creatively using the Reciprocal Teaching learning model.